ANALISIS STRATEGI GURU DALAM MEMBANTU MEMBACA PEMAHAMAN SISWA KELAS III PADA PROSES PEMBELAJARAN BAHASA INDONESIA DI SDN TELANG 1 - Aisyah, Siti; Agung Setyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension is one of the basic skills that elementary school students must have because it plays an important role in understanding information and supporting learning success. Students' reading comprehension still requires teacher guidance through the application of appropriate learning strategies. This study aims to describe the strategies teachers use to help students with reading comprehension and the obstacles teachers face in applying these strategies in Indonesian language lessons for third-grade students at SDN Telang 1. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation, and then analyzed using stages of data reduction, data presentation, and drawing conclusions, with triangulation techniques to test the validity of the data. The research results show that teachers use various strategies, such as taking turns reading, finding or noting difficult words, asking questions based on the reading content, retelling the content in their own words, and giving appreciation. The challenges faced include low student reading interest, students’ attention being easily distracted, limited student vocabulary, and limited learning media.